Probing recalcitrant problems in polyclad evolution and systematics with novel mitochondrial genome resources - Kenny, Nathan J. (2019)
For their apparent morphological simplicity, the Platyhelminthes or “flatworms” are a diverse clade found in a broad range of habitats. Their body plans have however made them difficult to robustly classify. Molecular evidence is only beginning to uncover the true evolutionary history of this clade. Here we present nine novel mitochondrial genomes from the still undersampled orders Polycladida and Rhabdocoela, assembled from short Illumina reads. In particular we present for the first time in the literature the mitochondrial sequence of a Rhabdocoel, Bothromesostoma personatum (Typhloplanidae, Mesostominae). The novel mitochondrial genomes examined generally contained the 36 genes expected in the Platyhelminthes, with all possessing 12 of the 13 protein-coding genes normally found in metazoan mitochondrial genomes (ATP8 being absent from all Platyhelminth mtDNA sequenced to date), along with two ribosomal RNA genes. The majority presented possess 22 transfer RNA genes, and a single tRNA gene was absent from two of the nine assembled genomes. By comparison of mitochondrial gene order and phylogenetic analysis of the protein coding and ribosomal RNA genes contained within these sequences with those of previously sequenced species we are able to gain a firm molecular phylogeny for the inter-relationships within this clade. Our phylogenetic reconstructions, using both nucleotide and amino acid sequences under several models and both Bayesian and Maximum Likelihood methods, strongly support the monophyly of Polycladida, and the monophyly of Acotylea and Cotylea within that clade. They also allow us to speculate on the early emergence of Macrostomida, the monophyly of a “Turbellarian-like” clade, the placement of Rhabditophora, and that of Platyhelminthes relative to the Lophotrochozoa (=Spiralia). The data presented here therefore represent a significant advance in our understanding of platyhelminth phylogeny, and will form the basis of a range of future research in the still-disputed classifications within this taxon.